Analysis of Teacher Competence Using ICT in Learning After Pembatik (Pembelajaran Berbasis TIK) Program Implementation - Lumbantobing, Panca; Syaodih, Ernawulan (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2024)
The aim of this study is to search the impact of the PembaTIK Program on the competence of teachers in the use of ICTs in learning after the implementation of the ICT-based Learning Program (PembaTik). The PembaTIK Program, which is run by the Badan Layanan Teknologi (BLPT) Ministry of Education, Culture, Research and Technology, aims to improve teacher competence in using ICT in learning. The research method used is a case study approach with research subjects consisting of 10 teachers who have completed the PembaTIK Program to level 3 and are passing level 4 by 2023 in the northern Sumatera province. Data is collected through interviews and analyzed using a thematic approach. The result of the research was that the PembaTIK Program improved the competence of teachers in the use of ICTs in learning. The improvement in the teacher's competence after following is that teachers have improved the skills of the tick in teaching. It can be seen from how teachers prepare to plan innovative and creative learning with the help of ICT. It is in the teaching that PembaTik can increase the learning interest of pupils; PembaTik also help teachers do good practice and share knowledge with teachers' peers and the teacher community by becoming a source, besides acting as a program that helps teachers continue learning and improve teacher competence. proves that all teachers who become sources continue to follow a PembaTik program every year because it can motivate teachers into learning and sharing good practices with other teachers.